Diabetes control could through platelet-to-lymphocyte ratio in hemograms - Atak,Burcin (2019)
SUMMARY OBJECTIVE Association between type 2 diabetes mellitus and inflammation is well-established. We aimed to study platelet-to-lymphocyte ratio (PLR), a novel inflammatory index derived from hemogram, in diabetic patients in comparison to those in healthy volunteers. METHODS Medical data of type 2 diabetics that showed up in general outpatient medical clinics of our institution between February 2017 and August 2017 were recorded and analyzed. RESULTS Median PLR of type 2 diabetic patients was significantly higher than the PLR of healthy controls (p=0.001). Moreover, PLR was significantly and positively correlated with HbA1c (p<0.001, r=0.58), fasting plasma glucose (p<0.001, r=0.49), and c-reactive protein (p=0.003, r=0.30) levels. Type 2 diabetic subjects with proteinuria had significantly higher PLR levels than that of diabetic subjects without proteinuria. CONCLUSION As an inexpensive and easy to use index, PLR may be useful in predicting the development and control levels of type 2 diabetes mellitus. However, its correlation with HbA1c needs to be validated by larger prospective studies.